Color changes of polyetheretherketone (PEEK) and polyoxymethelene (POM) denture resins on single and combined staining/cleansing action by CIELab and CIEDE2000 formulas - Polychronakis, Nick; Lagouvardos, Panagiotis; Polyzois, Gregory; Sykaras, Nikitas; Zoidis, Panagiotis (Journal of prosthodontic research, 2020)
The purpose of study was to investigate the long-term effect of staining and/or cleansing solutions on the color stability of two non-metal removable partial denture materials. One hundred disks (25×3mm) of polyoxymethylene (POM) and polyetheretherketone (PEEK) were immersed in water, wine, coffee, cleanser and combo bath, simulating normal daily use. Color parameters in the CIELAB system was measured every 30 cycles up to 240 using a contact colorimeter and color differences estimated using ΔEab and ΔE00 formulas. Two-way repeated measures ANOVAs and regression analyses were performed at α=0.05. Regression analysis indicated a strong R2 between color changes and number of cycles, for both materials. Tests of within-subjects effects for the ΔEab revealed significant differences among cycles and between the materials in the wine and coffee baths (p<0.001). Significant materialXcycles interactions were also recorded with all staining baths. ΔE00 values were lower than ΔEab up to 63.6%. Tests within and between-subjects effects for the ΔE00 gave similar but not the same with ΔEab results. ΔE00 found to correlate well with ΔEab. Long term exposure of both materials showed a progressive discoloration in all except control baths. POM discolored more than PEEK in coffee, and combo baths but not in cleanser. Discoloration was smaller in combo bath (where a cleanser was also used) indicating the effectiveness of a cleanser to prevent long term discoloration of both materials.